How to win friends and influence people - Carnegie, Dale (Vermilion, 2004)
This is one of the most influential business and communication skills guide. This book teaches you how to market yourself and generate more clients. This book has been acclaimed by many known figures around the world. This book tries to get you out of a mental hell and provides you with ambition and goals. It enables you to be friendlier and seem a positive person to others, it helps you become a popular person who is liked by the majority and in business terms, it enables you to win new clients. it increases your earning power by helping you use your potential to the fullest and it helps you to become a better public speaker and to be liked by mass audience.